PARTISIPASI PEMUDA DALAM PENGEMBANGAN DESA WISATA DI KELURAHAN BUDAYA PAMPANG KECAMATAN SAMARINDA UTARA KOTA SAMARINDA - Zulfadlian Nur (Magister Administrasi Publik FISIP Universitas Mulawarman, 2020)
The purpose of this study is to describe youth participation in the development of tourism villages in Pampang Cultural Village, Samarinda City. The research method used is a qualitative descriptive approach. Analysis of the data used in this study is the analysis of interactive model data. The results showed that the participation of youth in the development of a tourist village in Pampang Budaya Village was demonstrated by active participation in providing input, implementation, and implementation such as performing traditional dances, making handicrafts and mutual assistance as well as participating in enjoying the results and participating in evaluating the development of tourist villages.Keywords: Participation, Youth, The Village Tourist